2021
DOI: 10.1016/j.heliyon.2021.e07894
|View full text |Cite
|
Sign up to set email alerts
|

The relation between oxytocin receptor gene polymorphisms, adult attachment and Instagram sociability: An exploratory analysis

Abstract: Oxytocin is a primary neuropeptide which coordinates affiliative behavior. Previous researchers pointed to the association between genetic vulnerability on Oxytocin Receptor Gene ( OXTR ) and environmental factors (e.g., social relationships) to comprehend social behavior. Although an extensive knowledge of in-person social interactions has been obtained, little is known about online sociability. A gene-environment perspective is adopted to examine how … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 125 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…The issue seems to have been exacerbated by COVID-19-related lockdown restrictions, which turned online interaction into the only viable option for many [61,62]. In view of its major relevance, the topic of social media behaviour and its related pathologies has been investigated from several disciplinary angles [63], with a view to developing effective strategies to cope with problematic and socially critical situations [64]. Our paper, in line with the existing literature [43], did not find significant gender differences in SN addiction.…”
Section: Discussionmentioning
confidence: 99%
“…The issue seems to have been exacerbated by COVID-19-related lockdown restrictions, which turned online interaction into the only viable option for many [61,62]. In view of its major relevance, the topic of social media behaviour and its related pathologies has been investigated from several disciplinary angles [63], with a view to developing effective strategies to cope with problematic and socially critical situations [64]. Our paper, in line with the existing literature [43], did not find significant gender differences in SN addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Variables regarding participants’ sleeping patterns were weekday bedtimes, wake up times, and total sleep time; weekend bedtimes, wake up times, and total sleep time; weekend sleep delay, weekend oversleep, daytime sleepiness, sleep/wake behaviour problems, circadian preference, and caffeine consumption. Two Bonferroni corrections were computed to adjust the significance levels and to control for false-positive results (i.e., type I error) in a conservative way [ 56 ]. The first Bonferroni correction was computed to interpret the results regarding the influence of demographic variables on sleeping patterns.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Romantic love and psychological intimacy play more important roles in marriages in individualistic cultures (compared with collectivistic cultures). In collectivistic cultures, relationship with other family members (e.g., parents, siblings, and in-laws) has an important position (Wong and Goodwin, 2009;Chiu and Hong, 2013;Carollo et al, 2021). Crosscultural studies of love and intimacy have reported differences between individualistic and collectivistic cultures.…”
Section: Limitations and Future Researchmentioning
confidence: 99%